2020
DOI: 10.12965/jer.2040340.170
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a 12-week training program on the anthropometric and physiological profiles of some participants registered in a fitness center in Douala, Cameroon

Abstract: Fitness centers are remarkably abundant in Cameroon. The aim of this work was to assess the effects of a 12-week training program on the anthropometric and physiological profiles of some participants in a fitness center. A total of 86 participants (40 from the experimental group and 46 from the control group) with age ranging from 17 to 53 years were subjected to pre-and posttraining assessments of, anthropometric parameters, physiological parameters, and performance. Anthropometric parameters (weight, height,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Physical activity and nutritional pattern can positively affect the immune system and production of white blood cells [8,9], but recent studies have had contradictory results; some have suggested that high-intensity physical activity can increase the level of inflammatory indicators, while others have shown no effect [10][11][12][13]. This clinical trial aims to investigate the effects of 8 weeks of functional training and online nutrition education on inflammatory biomarkers in children with ASD aged 8-12 years during the Covid-19 pandemic in Tehran, Iran.…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity and nutritional pattern can positively affect the immune system and production of white blood cells [8,9], but recent studies have had contradictory results; some have suggested that high-intensity physical activity can increase the level of inflammatory indicators, while others have shown no effect [10][11][12][13]. This clinical trial aims to investigate the effects of 8 weeks of functional training and online nutrition education on inflammatory biomarkers in children with ASD aged 8-12 years during the Covid-19 pandemic in Tehran, Iran.…”
Section: Introductionmentioning
confidence: 99%